2013
DOI: 10.1039/c2ta00776b
|View full text |Cite
|
Sign up to set email alerts
|

Pt–Au/nitrogen-doped graphene nanocomposites for enhanced electrochemical activities

Abstract: A facile in situ assembly strategy was developed for the fabrication of Pt-Au alloy nanoparticles (NPs) on nitrogen-doped graphene (N-G) sheets, and the as-fabricated Pt-Au/N-G nanocomposites were suitable for electrochemical applications. As characterized by transmission electron microscopy, X-ray photoelectron spectroscopy, X-ray diffraction analysis and inductively coupled plasma-atomic emission spectroscopy techniques, Pt-Au alloy NPs with an average size of 4-5 nm were uniformly distributed on the N-G sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(72 citation statements)
references
References 69 publications
3
68
0
1
Order By: Relevance
“…Moreover, nitrogen doping could introduce active sites for catalytic reactions and also act as anchoring sites for metal nanoparticle deposition. Yang et al fabricated a composite of Pt-Au alloy nanoparticles on NG sheets by a wet-chemistry method [127]. As shown in Figure 7, the NG was synthesized by thermal treatment of GO powder and melamine.…”
Section: Ng As Support Materials For Orrmentioning
confidence: 99%
“…Moreover, nitrogen doping could introduce active sites for catalytic reactions and also act as anchoring sites for metal nanoparticle deposition. Yang et al fabricated a composite of Pt-Au alloy nanoparticles on NG sheets by a wet-chemistry method [127]. As shown in Figure 7, the NG was synthesized by thermal treatment of GO powder and melamine.…”
Section: Ng As Support Materials For Orrmentioning
confidence: 99%
“…The Pt nanoparticles exhibit an average size of 2.2 ± 0.6 nm. Figure 11.10a shows a single platinum nanoparticle exhibiting 2.25Å lattice fringes corresponding to the (111) planes of a face-centered cubic structure [17]. …”
Section: Bovine Bone-platinum Compositesmentioning
confidence: 99%
“…Studies have indicated that nitrogen-doped graphene has a larger area and shows an enhanced electronic activity [9][10][11] . In addition, nitrogen-doped graphene is a good carrier of other guest molecules or materials, which may provide the nanomaterial new characteristics [12] . Meanwhile, Cu 2 O is an important p-type semiconductor with a band gap of 2.17 eV, and has been widely used in solar energy conversion [13] , photocatalytic degradation [14] , and electrochemical sensing [15] .…”
Section: Introductionmentioning
confidence: 99%